Potencial alelopatico e citogenotóxico de Eugenia florida DC em bioensaios com Lactuca sativa L - Alves, Pâmela Ingrid (2019)
The search for herbicides that have less impact on the environment and human health has become a constant challenge. In this context, the use of plant extracts with allelopathic activity has become a viable option for farmers, which has shown a great acceptance in the consumer market, considering the low cost and easy production, thus promoting benefits to the environment and to man. The Eugenia florida species demonstrates in its chemical characterization the presence of inducing and inhibiting compounds for germination and seedling growth. However, its activity is still unprecedented. In addition, the influence of the light exposure of the leaves are factors that interfere in the quantity and quality of the compounds produced by the plant. Leaves located on the periphery (exposed to the sun) of the crown tend to have a greater diversity and amount of compost. The extraction methods used for the production of the extracts influence the amount and the compound that will be extracted. Thus, this work aimed to elucidate the phytotoxic and cytogenotoxic properties of the leaves of the periphery and the interior of the canopy of Eugenia Florida, using both aqueous and hydroethanolic forms of extraction on bioassays with L. sativa. The germinative parameters, such as initial growth and the behavior of the chromosomal complement, were evaluated. For data analysis, was used ANOVA analysis of variance and the means were compared using the Scott knott means test, at 5% significance for the extracts. For concentrations, the regression model was adjusted to 5% significance. Results demonstrated that all extracts have allelopathic activity, that is, they interfere with the germination and initial growth of seedlings, been the most responsive in the highest concentration. Furthermore, the position of the leaves and the extraction method for the preparation of the extract only influence in intermediate concentrations, which the leaves from the periphery and aqueous extraction were most efficient. In addition, all extracts have an influence on the cell cycle, with a reduction in the mitotic index followed by an increase in concentrations. This dissertation is presented in the form of chapters. Chapter I presents a brief review of the family Myrtaceae, the genus Eugenia and the species Eugenia florida; allelopathy; secondary metabolites; the mechanism and mode of action of allelochemicals and the importance of bioassays for allelopathic and cytotoxic analyzes. Chapter II is presented in the form of scientific article, formatted according to the guidelines of the journal Environmental Sciences.